Investigating H3K4 methylation by SET1/MLL complexes - Au, HYA (2023)
H3K4 methylation is a histone modification which often correlates well with active transcription. In mammals, the SET1/MLL complexes are responsible for H3K4 methylation. The conventional view holds that SET1A/B complexes deposit the majority of H3K4me3 at highly-transcribed genes, MLL1/2 complexes deposit H3K4me3 at a subset of lowly-transcribed genes, and MLL3/4 complexes deposit H3K4me1/2 at enhancers. In mammals, H3K4me3 is found at CpG islands - short stretches of DNA with high CpG density that remain unmethylated in an otherwise pervasively methylated genome. The SET1A/B and MLL1/2 complexes all contain a zinc-finger CXXC domain that targets them specifically to CpG islands. Over 70% of all promoters contain a CpG island, and SET1A/B and MLL1/2 complexes were thought to promote transcription by creating a permissive chromatin state through H3K4me3 deposition. However, recent work has shown that SET1A/B complexes can support transcription through an H3K4me3-independent mechanism, and their removal results in surprisingly modest reductions in H3K4me3. Therefore, our understanding of the how SET1/MLL complexes deposit H3K4 methylation and how they regulate transcription is lacking.